Analysis, Typology, and Chronology of Stuccos in the Palace of Kuh-e Khvājeh - VASEGH ABBASI, Zoheir; MEHRAFARIN, Reza; MOSAVI HAJI, Seyyed Rasol (Historia i Świat, 2018)
Due to its strategic and unique location, Mount Oshida (Kuh-e Khvājeh) in the Sistān plain, has been alternatively used since a long time ago to this date. On the southern slope of this mountain, the ruins of a palace known as Qalʿa-ye Kāferān appear after the Muslims’ arrival and domination over the region. This castle was explored and excavated during the second and third decades of the twentieth century by scholars such as Stein and Herzfeld, and its decorations have been widely mentioned. However, its stuccos have not been analyzed in terms of their types, forms, and patterns up to this date. Hence, there are some disagreements about their construction date, as some scholars consider these architectural decorations to belong to the Parthian period while others connect them with the Sasanian period. In the present research, it has been attempted to study and evaluate the stuccos in the palace of Kuh-e Khvājeh in the framework of a typological comparison according to the archaeological evidence and historical documents, so that a clear understanding of the historical situation and construction date of these works can be obtained. The research method of the current study has been based upon documentary sources and archaeological evidence. Reviewing the previously performed studies and excavations, along with the comparison and typology of stuccos obtained from other sites, leads us to the conclusion that the stuccos found on this site belong to the Sasanian period in terms of shape, form and decoration.